The Importance of Optimizing Energy Consumption in Wastewater Treatment Plants- A Case Study of East Mashhad Wastewater Treatment Plant - Vahid Aghabalae; Naser Mehrdadi; Shima Mardani; Mahla Tabeshnia (علوم و مهندسی آب و فاضلاب, 2021)
Construction of wastewater treatment plant, if energy and water resources are recovered, can justify some undesirable effects such as greenhouse gas emissions. sludge management and treatment is one of the most complex and costly parts of treatment plants that can cover up to 60% of initial capital and operation costs of a wastewater treatment plant. Considering the importance of reducing energy consumption in wastewater treatment plants as an environmental and economic point of view, some investigations have done to construct and modify wastewater plants worldwide in order to the self-sufficiency of energy supply recently year. This article is a practical study that the costs of capital and energy consumption were analyzed in comparison with other processes for MLE1 process with aerobic digestion in wastewater treatment plant in east of Mashhad with flow rate of 80000 m3/d. The results show that energy consumption in this system is about 2 times of similar wastewater treatment plants with optimal process. Also, however, the energy level will decrease from 1 kwh/m3 to 0.58 kwh/m3 with the change of aerobic digestion to anaerobic, but it is necessary to use of CHP system for decrease of energy consumption and recovery in comparison with constructed or optimized of wastewater treatment plants in worldwide. Therefore, it is necessary to pay more attention in selecting the process of liquid and sludge section in wastewater treatment plants under studying or optimizing wastewater treatment plants built in the country because of the numerous benefits of reducing energy consumption in wastewater treatment plants, in order to be self-sufficient in energy supply.